PERAN CORPORATE GOVERNANCE PADA HUBUNGAN DEFAULT RISK DENGAN EARNING RESPONSE - Hermanto Hermanto; Ni Ketut Surasni; Firmansyah Firmansyah (Master of Management, Mataram University, 2019)
Company default risk will determine investor reaction on the increase of company earning. If financial statements contain information, then financial markets will react as a result of reported earnings. The primary focus of this study aims at analyzing the impact of default risk on earning response coefficient as well as the influence of corporate governance toward the connection between default risk and earning response coefficient. In addition, this study examines the influence of size and growth opportunity toward the earning response coefficient. This is a cross sectional study, analyzing year 2017 sample data. The research sample consists of 49 companies taken purposively from the list of companies in Indonesia Stock Exchange. Results of this study prove that default risk has a negative impact on earning response coefficient and that corporate governance can reduce the negative impact of default risk on earning response coefficient. This study also finds evidence that growth opportunity positively influences earning response coefficient. Keywords: corporate governance; default risk; earning response coefficient; growth opportunity